MODEL PENGEMBANGAN EKONOMI PARIWISATA - Hasan, Ali; Hermawan, Budi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
This paper reviews previous models of economic development of tourism using models such as pentahelix which generally focus more on how synergy and synchronization of government, academic, business, media, and tourism institutional actors, as well as the Tourism Satellite Account which methodologically measures only the end result tourism, while the power of the sector of economic potential and the transition of natural resource-based economic potential into a tourism-based economy has not been taken into account. Therefore such a perspective reflects only a narrative, but there is no model that mathematically explains the effect of the shift of the leading economic sector to GDP. Economic sustainability is a useful and useful purpose for human survival, therefore the model of economic development of tourism in the economic development of this society can complement the previous models, theoretically described the concept of economic development of tourism, model, measurement, program and indicators of development success tourism economy. Keywords: economic power of tourism, excellence sector and measurement of tourism economy